USE OF NEW TECHNOLOGIES IN TRANSPORT LOGISTICS BY BUSINESS STRUCTURES - Андрусів, Уляна Ярославівна; Зелінська, Галина Олексіївна (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2025)
It was determined that among the main problems that require urgent solutions in the field of transport logistics, it is necessary to highlight the insufficient efficiency of planning and optimizing transport routes, which leads to excessive fuel consumption and increased delivery time; high operating costs for maintenance and operation of vehicles, which make up a significant share of total logistics costs; difficulties in managing inventories and coordinating interaction between various participants in the logistics chain, which affects the overall efficiency of the system; insufficient transparency and traceability of logistics processes, which complicates service quality control and risk management. The efficiency indicators were analyzed, which indicates that each of the technologies considered makes a unique and specific contribution to increasing the overall efficiency of logistics operations, while the greatest economic effect is achieved with the comprehensive implementation of several complementary technological solutions that create a synergistic effect and allow for maximum use of the potential of digital transformation. Attention is focused on the fact that the successful implementation of new technologies requires a comprehensive and systematic approach, which includes careful strategic planning taking into account the specific features and needs of a particular enterprise, significant investments in modern technological infrastructure and software, targeted development of human resources through training and retraining of personnel, and the creation of an effective change management system. It has been determined that issues of cybersecurity and protection of confidential data are becoming particularly important in the context of the growing digitalization of logistics processes, as the increase in the number of digital channels of interaction and information exchange creates new vulnerabilities and risks for the security of corporate data, personal customer information, and confidential commercial information, which requires significant investments in information protection systems and constant monitoring of threats.